(untitled) (Al-Academy, 2026)
The research deals with the study of the expressive values of fabrics and costumes in the scenography of theatrical performance as one of the important elements in the theatrical performance because it occupies a physical space above the stage and at the same time contributes to conveying the general meaning through the values that are represented in it. The research falls into four axes. The first chapter includes the research problem. Which was crystallized in the following question (Was the designer of fabrics and costumes in the theater able to achieve an artistic effect and an aesthetic presence through the intersection of the relationships of fabrics and costumes with the rest of the elements and components of scenography)، in addition to the importance of the research and the objectives of the research، which are to identify the expressive values and designs of fabrics and costumes and their role in the scenography of the show? Theatrical and definition of terminology. In the second chapter (theoretical framework)، two sections included the first section: the expressive values in the designs of fabrics and fashions. The second section is the concept of scenography. The third section is the research procedures، the research community، and the research sample. The results that were discussed in the fourth chapter appeared، and through it the conclusions were reached and recommendations were presented. The researcher is capable of developing the task of performing elements of fabrics and costumes in the scenography of theatrical performance.